2006
DOI: 10.1002/eat.20347
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mental health problems and negative caregiving experiences in carers of adolescents with bulimia nervosa

Abstract: Interventions focusing on reducing EE and contact hours could prove beneficial for both patient and caregiver outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
2
6

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 34 publications
4
62
2
6
Order By: Relevance
“…92 Carers of individuals with AN and BN have high levels of psychological distress. 93,94 Finally, eating disorders result in significant economic burden and health service use. A recent study on hospital admissions for adult psychiatric illness in England found that eating disorders had the highest proportion of admissions of all psychiatric disorders, with a length of stay over 90 days (26.8%) and the longest median length of stay (36 days).…”
Section: Limited Life Activitiesmentioning
confidence: 99%
“…92 Carers of individuals with AN and BN have high levels of psychological distress. 93,94 Finally, eating disorders result in significant economic burden and health service use. A recent study on hospital admissions for adult psychiatric illness in England found that eating disorders had the highest proportion of admissions of all psychiatric disorders, with a length of stay over 90 days (26.8%) and the longest median length of stay (36 days).…”
Section: Limited Life Activitiesmentioning
confidence: 99%
“…En contraposición se defi niría como cuidador secundario (CS), a la persona que pasa un menor tiempo de contacto personal. Esta definición ha sido utilizada previamente en varios estudios británicos (Sepulveda, Lopez, Todd, Whitaker, y Treasure, 2008;Whitney, Haigh, Weinman, y Treasure, 2007;Winn et al, 2006). En general, poco sabemos sobre la presencia de psicopatología en estos familiares y si a su vez, hay diferencias entre el tipo de cuidadores debido a la convivencia con pacientes que tienen blación no clínica.…”
Section: Instrumentosunclassified
“…En este sentido, Sanjuán, Pérez-García, Rueda y Ruiz (2008) han encontrado una mayor asociación de este estilo explicativo con los síntomas de ansiedad. Winn et al (2006) encuentran otros factores, en familiares de pacientes de TCA, como el mayor número de horas de contacto con el paciente y valores altos en la emoción expresada. Otros estudios muestran que los familiares se acomodan a los rituales y conductas alimentarias nocivas como un «estilo de vida», adaptando su rutina y funcionamiento familiar a las exigencias de la patología (Sepúlveda et al, 2009).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…17 Bulimic phenomenology also negatively impacts the interpersonal functioning of caregivers. 18 The association of interpersonal problems and bulimia suggests that accounting for interpersonal difficulties might enhance therapeutic effects and reduce dropout and remission rates. For example, clients could be matched to therapists and therapies well-suited to address their interpersonal difficulties, or specific techniques could be used to augment the ability of common contemporary treatment strategies to address relational issues.…”
Section: Introductionmentioning
confidence: 99%